2005
DOI: 10.1021/ma052166w
|View full text |Cite
|
Sign up to set email alerts
|

Onsets of Tethered Chain Overcrowding and Highly Stretched Brush Regime via Crystalline−Amorphous Diblock Copolymers

Abstract: Lamellar single crystals grown in dilute solutions can be used as templates for tethered chain analysis. Two series of diblock copolymers, poly(ethylene oxide)-block-polystyrene (PEO-b-PS) and poly(Llactic acid)-block-polystyrene (PLLA-b-PS), were used as model templates to generate tethered PS blocks on the single-crystal basal surfaces. Controlled and tunable reduced tethering density, σ ˜, defined by σπR g 2 (where σ is the tethered chain density and is equal to the reciprocal of the covered area of the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
178
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(192 citation statements)
references
References 60 publications
12
178
2
Order By: Relevance
“…In our work, the lens-shaped crystals were also observed for the homo-PEG 5000 . The lens-shaped crystals were previously reported for PS-b-PEO by Zheng and co-authors [55].…”
Section: Rectangular/hexagonal Dielectric Peg Single Crystalssupporting
confidence: 59%
See 2 more Smart Citations
“…In our work, the lens-shaped crystals were also observed for the homo-PEG 5000 . The lens-shaped crystals were previously reported for PS-b-PEO by Zheng and co-authors [55].…”
Section: Rectangular/hexagonal Dielectric Peg Single Crystalssupporting
confidence: 59%
“…In conclusion, the relation applied for the grafting density of conventional homo-brush single crystals (Eq. 2) [55] was not more usable for the random single-cocrystals.…”
Section: Homopolymer/block Copolymer Single-co-crystalsmentioning
confidence: 95%
See 1 more Smart Citation
“…13,29 Furthermore, to our knowledge, the use of different seeds from the same polymer to induce the formation of 2D platelets of different shape via seeded growth in solution is unprecedented. Analysis by selected area electron diffraction (SAED) analysis revealed that the quasi-hexagonal disk-like and rectangular platelets (grown from 2D seedHD and 2D seedR1, respectively) have near identical ED patterns with three pairs of diffraction spots, confirming the presence of a single crystalline PFS core with monoclinic symmetry (Fig.…”
Section: Seeded Growth Of Pfs Homopolymers With Charged End-groups Usmentioning
confidence: 99%
“…8,9 Recent advances have demonstrated the use of thiol-terminated crystalline homopolymers that allow the peripheral nanoparticle patterning on the 2D platelet, 10,11 as well as the fabrication of alternate rings of a homopolymer and BCP. 12,13 In a further advance, nanosheets formed by the crystallization of precursors containing silsesquioxane clusters bound to hyperbranched polymers can be fragmented into seeds using sonication which can be used to control the growth of 2D platelets on subsequent precursor addition. 14 We have shown that addition of a BCP with a crystallizable poly(ferrocenyldimethylsilane) (PFS) core-forming block 15 and a short complementary corona-forming block to seeds derived from the sonication of 1D cylindrical PFS BCP micelles allows access to lenticular platelet micelles.…”
mentioning
confidence: 99%